The relationship between gestures and non-verbal communication and attentional processing in high-functioning adolescents with autism spectrum disorder. (July 2018) - Pudło, Monika; Pisula, Ewa
Background and aims: The links between gestures and various attentional processes in adolescents with autism spectrum disorder have not been studied sufficiently. Previous studies have highlighted the impact of orienting attention on the efficacy of gestures without exploring the influence of alerting and top–down attentional processes. The aim of the present study was to explore the links between attentional processes and indicators of descriptive, conventional and emotional gestures as well as other aspects of nonverbal communication in adolescents with autism spectrum disorder ( N  = 46). Methods: The attention network test and colour trails test were used to measure attentional processes, whereas descriptive, conventional and emotional gestures were assessed using the Autism Diagnostic Observation Schedule and the autism diagnostic interview . Analysis showed a significant correlation between gestures with alerting, orienting and executive attention. Conclusions: The relevant structural equation model revealed that attentional processes have an impact on gestures, but gestures do not have an impact on attentional processes. Emotional gestures are linked to alerting. Spatial-visual search was related to facial expression and the integration of nonverbal communication with behaviour. There was no significant interaction between executive attention and gestures. Implications: The obtained results are discussed with reference both to gesture development and studies on attention in adolescents with autism spectrum disorder.